The The Impact of Implementing Fair Trade the Body Shop Community On Shea Farmers In Ghana - Kuswaya, Nabilla Chaerunnisa; Muslikhati , Siti (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The development of globalization has an influence on trade. Especially with the emergence of free trade. Through the concept of open trade, free trade seeks to provide access to prosperity. However, in practice, this access can only be enjoyed by countries with advanced scientific and technological development. Meanwhile, countries in Africa such as Ghana seem to be victims of free trade through the exploitation of developed countries. This makes economic inequality increasingly visible, and this situation attracts the attention of a group of people to present a solution by creating a fair-trade system that favors the profits of local companies and producers. The Body Shop ads is one of the agents that carries out fair trade which as of this writing will operate in Northern Ghana through the empowerment of northern Ghanaian farmers which is implemented by forming a shea farming community called "Tungteiya Woman". This research was conducted trying to combine the theory of power relations with the concept of sustainable development and the implementation of fair trade carried out by The Body Shop. The research method in this paper uses qualitative methods sourced from secondary data through literature study techniques obtained from books, journals, and articles. Research shows that the existence of The Body Shop in running a fair-trade community in Northern Ghana has had a positive impact on the economy of shea farmers by implementing the 10 principles of fair trade.